Redbay Ambrosia Beetle-Laurel Wilt Pathogen: A Potential Major Problem for the Florida Avocado Industry - Jonathan H. Crane; Jorge E. Peña; J. L. Osborne (EDIS)
HS1136, a 7-page illustrated factsheet by Jonathan H. Crane, Jorge Peña, and J.L. Osborne, describes this insect-fungal pest attacking woody plants in the laurel family, including avocado. Includes descriptions, origin, detection and spread of the pest, plant hosts in the U.S., a map of counties with the beetle, plant host symptoms and damage, management strategies & restrictions, agencies working on the issue, research and extension efforts, and references. Published by the UF Department of Horticultural Sciences, February 2008. Revised December 2008.